Grazing Communities Pastoralism on the Move and Biocultural Heritage Frictions (Volume 29) - Bindi, Letizia (Berghahn Books, 2022)
Pastoralism is a diffused and ancient form of human subsistence and probably one of the most studied by anthropologists at the crossroads between continuities and transformations. The present critical discourse on sustainable and responsible development implies a change of practices, a huge socio-economic transformation, and the return of new shepherds and herders in different European regions. Transhumance and extensive breeding are revitalized as a potential resource for inner and rural areas of Europe against depopulation and as an efficient form of farming deeply influencing landscape and functioning as a perfect eco-system service. This book is an occasion to reconsider grazing communities' frictions in the new global heritage scenario.